Accountability of village funds: Through competence and SISKEUDES, supervision moderation and leadership style - Dewi, Ni Sayu Kadek Era Susipta; Yamin , Nina Yusnita; Kamase, Haryono Pasang; Pakawaru, Muhammad Ilham; Erwinsyah, Erwinsyah (Master in Accounting Program, Faculty of Business & Economics, Universitas Islam Indonesia, Yogyakarta, Indonesia, 2025)
The key to achieving excellent governance lies in the effective management of village funds. The aim of this research is to examine how the competence of village officials, the utilization of the Village Financial Information System (SISKEUDES), and the discipline of supervision and leadership style affect the accountability of village fund management. This research was conducted on village officials in all villages in Lariang District, Pasangkayu Regency, totaling 63 people who were determined purposively. A questionnaire was used to gather primary data, and the Partial Least Square (PLS) method was used for analysis. The research's findings demonstrate that the accountability of village fund management is significantly improved by the capability of the village apparatus and the application of SISKEUDES. These results indicate that achieving transparent and accountable village fund management requires both enhancing the apparatus's knowledge and abilities, and making the best use of the village financial information system. These results strengthen the argument in contingency theory. Furthermore, the impact of the competence of village officials and the application of SISKEUDES on the village fund management’s accountability is not influenced by supervision or leadership style. In addition, this research has implications for strategies to enhance the village fund management’s accountability. Such strategies could include enhancing the competence of village officials and maximising the usage of SISKEUDES.